Analysis of stress through salivary and blood cortisol: systematic review - Polonia, Faviola Esther Antonio (2023)
Stress in health area, generally has been measured by objective and subjective means. Subjective data through answering questionnaires, forms, visual and analog scales, are important to identify stress level. However, the dosage of blood and saliva cortisol can provide better indicators for the objective assessment of stress level. The aim of this systematic review was to investigate studies that evaluated and compared stress levels through blood (gold standard) and salivary cortisol levels, identify whether or not correlation between levels of these biomarkers during stressful situations. Saliva samples are easier to obtain than blood samples and may be more suitable for experimental studies evaluating stress level. Methods: a meticulous electronic literature search was performed in PubMed; Scopus; VHL Regional Portal; Embase and Web of Science, searches were carried out up to January 2023, using descriptors and keywords concerning to: cortisol, saliva, blood, serum, plasma and stress, combined and co-related with each other, and also their possible synonyms in English, Portuguese and Spanish. The studies were analyzed by two independent reviewers in order to meet the inclusion criteria. Results: initial search found, 1,054 scientific studies, 216 selected articles after reading the titles and abstracts that meet the eligibility criteria. With the complete reading of the articles were selected 68, but finally 34 articles met all the inclusion and exclusion criteria established in this systematic review. The scientific studies that entered in our systematic review could be divided into six lines: 1) Psycological stress [6 articles found]; 2) Drugs that could influence the stress level [5 articles found]; 3) Stress related to stopping smoking [3 articles found]; 4) Stress in sports activities and exercises [2 articles found]; 5) Stress related with sleep deprivation [1 articles found]; and 6) Stress in surgical patients [1 article found]; Our results showed a constant and consistent relationship between the levels of these hormones when analyzed in saliva and plasma, both in baseline situations and after acute stress situations (around 0.04). Given the above results, we concluded that cortisol collected in saliva can be used as a reliable biomarker against the gold standard (plasma) in scientific research. Conclusion: Given the above, we concluded that cortisol collected in saliva can be used as a reliable biomarker against the gold standard (plasma) in scientific research.